Production of a superhydrophobic frame-cone structure by laser etching and Ni electrodeposition. (2nd January 2023) - Liu, Hao; Di, Yuelan; Wang, Haidou; Zhao, Yuncai
ABSTRACT: Metal components in microelectromechanical systems are prone to failure and corrosion due to droplet adhesion in wet environments. Several multi-level structures on the micro-nano scale may induce effective superhydrophobicity to prevent such adhesion. This study proposes a hybrid manufacturing process to generate 'frame-cone' textures on the surfaces of metals by combining ultra-fast laser etching and electrodeposition. Periodically distributed frame recesses and pits were coated with nano-submicron Ni coatings with conical shapes, and the pit depth and cone height were controlled by tuning the laser scanning time and current density, respectively. The surface adhesion force was reduced to 22.8 μN, and the static contact angle was maintained at 156.7° using the hybrid process, while the adhesion forces of laser etched samples with the same depth were 164.7 μN. The multi-level 'frame-cone' structure stored more air and reduced the contact areas between the bottoms of the pits and droplets. The hybrid process of ultra-fast laser etching and electrodeposition aided in improving the superhydrophobicity, with less damage to the substrate.